Emerging risk factors and the disease pattern in Turkey: an analysis based on burden of diseases - Akgun, Seval H.; Nayar, Rajasekharan K. (International Journal Of Community Medicine And Public Health, 2021)
Knowledge about the burden of disease and injury alone is not sufficient for health improvement and for defining and evolving policies and strategies. In many low and middle income countries, the impacts of chronic diseases are increasing gradually each year. Anticipating, understanding and reducing the impact of chronic diseases on human health is of great importance. The aim of this paper was to assess the main risk factors in chronic diseases in a developing country and to identify the effects of individual risk factors on burden of disease by using comparative risk assessment methodology. The first BoD study in 2003 revealed that the high systolic blood pressure was ranked first and the prevention of high systolic blood pressure would prevent 108.468 of 430.459 deaths in Turkey. Smoking was at the second rank and prevention of smoking would prevent 54.699 deaths while control of cholesterol level within the normal limits would prevent 49.029 deaths. It is also indicated that adequate levels of physical activity would prevent 45.120 deaths and that consumption of the recommended amount of fruits and vegetables would prevent 38.734 deaths. In the 2013 study, smoking ranked first, followed by nutritional risks at the second rank followed by high BMI, high blood pressure and high sugar level respectively. Smoking, high blood pressure, obesity and tobacco use are the most important problems among the preventable deaths and disability in Turkey. It can be concluded that Turkey now resembles the pattern seen in developed countries and some developing countries with low mortality.